Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea - Frolová, Pavlína; Ďuriš, Zdeněk (Zootaxa, 2018)
A single ovigerous female specimen of marine shrimp of the family Palaemonidae collected from Madang Province, N.E. Papua New Guinea, was recognized as a representative of a new genus and species. Due to the presence of a sternal thoracic process, 3 pairs of posterior telson cuspidate setae, and the simple ambulatory dactyli, as well as the lack of branchiae on the two posterior maxillipeds, the new species clearly belongs to the assemblage of primarily free-living palaemonid taxa surrounding the speciose genera Cuapetes and Palaemonella. As the specimen possesses a short leaf-like rostrum, slender second pereiopods with small chelae similar to and not noticeably longer than the first pereiopods and very slender simple ambulatory dactyli, the specimen is without parallel within this assemblage and clearly represents a new genus. Its position within the Cuapetes/Palaemonella lineage of genera is also confirmed by a molecular comparison. The specimen is described and illustrated as a new genus and species.